“How to Turn a Dream into a Vocation” or Search for New Career Guidance Markers - Bielousova О. (New Collegium, 2021)
This article deals with the issue of preparing secondary school pupils to making their career choice as to the most important decision, which is to determine their subsequent life. The author emphasizes the topicality of the problem at the time when the labour market is undergoing substantial changes concerning the demand for professionals and requirements to them. The paper presents the experience of the People’s Ukrainian Academy in organizing vocational guidance work with schoolchildren, describes the newly-developed program for the formation of professional choice "How to turn a dream into a profession" and the mane years’ work of Entrepreneurship School. The author points out that career guidance could be much more effective if innovative techniques and approaches, as well as diverse formats of activities are employed. Involvement of all stakeholders and the focus on real needs and perspectives of Kharkiv region are also considered efficiency-boosting. The article also explicates the key principles of career guidance in PUA fostering its effectiveness.